A comparison between the powers of the PARBS and the RMBM - Miyashita, K.; Tsujino, Y.; Tokura, N. (IEEE First ICA³PP, IEEE First International Conference on Algorithms and Architectures for Parallel Processing, Brisbane, Australia, 19-21 April, 1995, 2002)
The Processor Array with Reconfigurable Bus System (PARBS) and the Reconfigurable Multiple Bus Machine (RMBM) are models of parallel computation based on reconfigurable bus and processor array. The PARBS is a processor array that consists of processors arranged to a 2-dimensional grid with a reconfigurable bus system. The RMBM is also made of processors and reconfigurable bus system, but the processors are located in a row and the number of processors and the number of buses are independent of each other. In this paper, we describe that the computational power of the PARBS is equal to that of the RMBM on condition that two models are polynomially bounded. This is because that one model can be simulated in constant time by another model.< >